2017
DOI: 10.1111/1440-1681.12892
|View full text |Cite
|
Sign up to set email alerts
|

Maternal protein malnutrition induced‐hypertension: New evidence about the autonomic and respiratory dysfunctions and epigenetic mechanisms

Abstract: SummaryMaternal protein malnutrition during the critical stages of development (pregnancy, lactation and first infancy) can lead to adult hypertension. Studies have shown that renal and cardiovascular dysfunctions can be associated to the development of hypertension in humans and rats exposed to maternal protein malnutrition. The etiology of hypertension, however, includes a complex network involved in central and peripheral blood pressure control. Recently, the hyperactivity of the sympathetic nervous system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…These behavioral alterations were not restricted to F1 generation only but also transmitted to following generation. These recent reports have further strengthened the idea that PMN results in neurobehavioral and epigenetic alteration leading to growth restriction and hypertension (de Brito Alves and Costa-Silva, 2018).…”
Section: Protein Malnutrition and Cns Developmentmentioning
confidence: 59%
“…These behavioral alterations were not restricted to F1 generation only but also transmitted to following generation. These recent reports have further strengthened the idea that PMN results in neurobehavioral and epigenetic alteration leading to growth restriction and hypertension (de Brito Alves and Costa-Silva, 2018).…”
Section: Protein Malnutrition and Cns Developmentmentioning
confidence: 59%
“…Arterial hypertension is a pathology with a multifactorial etiology, which may include renal alterations 33 , increase in the number of circulating catecholamines 34 , increase in peripheral vascular resistance 35 , sympathetic and respiratory changes 8 , among others. Respiratory function during development is an important prognostic factor for the course of neurogenic arterial hypertension and the expected lifespan of individuals who suffered perinatal undernutrition 1,7,36 .…”
Section: Discussionmentioning
confidence: 99%
“…In animals, a recent review showed accumulating evidence that, to a significant degree, the programmed hypertension may have a developmental origin, and the sympathetic-respiratory dysfunctions play an important role on the development of the maternal diet induced-hypertension 7,8 . Maternal protein restriction (8% casein) during gestation and lactation induced high respiratory frequency (RF) and respiratory chemosensitivity to O 2 /CO 2 9 .…”
Section: Introductionmentioning
confidence: 99%
“…19 The aetiology of hypertension in rats exposed to nutritional insults during pregnancy and/or lactation includes a complex network involved in central and peripheral blood pressure control. 20 Findings…”
Section: Re Sultsmentioning
confidence: 99%